The Influence of Integrated Planning Management of Qur'anic Values on Strengthening the Curriculum at Darul Falah Islamic Boarding School, West Bandung - Ahmad Andy Setiady; Mulyawan Safwandy Nugraha (Journal Research of Social Science, Economics, and Management, 2026)
The integration of Qur'anic values in the pesantren curriculum is a strategic need in the midst of the demands of modern education and needs to be managed managerially. This study aims to analyze the influence of Qur'anic value integration planning management on the strengthening of Islamic boarding school curriculum, which includes vision planning, needs analysis, strategy formulation, coordination, and continuous evaluation. The study used a descriptive-associative quantitative approach with a survey design on the management of IKSAN Pesantren Darul Falah West Bandung. The research instrument was tested using SPSS 26 with a Cronbach's Alpha value of 0.900 which indicates very high reliability. Data analysis included Shapiro–Wilk normality tests and simple linear regression. The results showed normal distribution data and a regression significance value of 0.000, which confirmed the significant influence of planning management on strengthening the pesantren curriculum. This study concludes that systematic and Qur'anic value-based planning is a key factor in strengthening the pesantren curriculum to be adaptive to the challenges of the 21st century.